Empowerment Journalism - Commentary for Special Issue of Journalism Studies. (10th September 2019) - Lefkowich, Maya; Dennison, Britney; Klein, Peter
ABSTRACT: Growing literature critiques the "parachute reporting" model of journalism. Briefly visiting communities as an outsider, overlooking local and cultural nuances, and prioritizing "audiences back home" can make this reporting practice problematic. Instead, we developed an approach called "empowerment journalism." Learning from foreign correspondence, citizen journalism, media activism, and community-based research, we challenge reporting inequities by centering on principles of accountability, reciprocity, collaboration, and local ownership. We develop community partnerships and work with story "subjects" to co-create content that matters to their communities. This commentary offers lessons learned from using this approach with varying levels of success across three projects. (1) In Strangers at Home, we launched a digital storytelling and social media project with members of marginalized communities about rising nativism in Europe. (2) In Through Somali Eyes, we collaborated with Somali journalists who documented their daily routines of reporting and navigating danger with wearable cameras. (3) In Turning Points, we are co-creating visual stories with Indigenous storytellers in Yellowknife that confront stereotypes about alcohol. By reimagining the "newsroom" within – rather than distinct from – communities, we illustrate tensions and opportunities for journalists to transition from gatekeeper to collaborator and empower story "subjects" to produce and own their content.